Abundance and diversity of thrips (Insecta Thysanoptera) in conventional "carabao" mango orchard in Piat, Cagayan, Philippines - Reyes, Cecilia P.; Cayabyab, Bonifacio F.; Copuyoc, Maria Katherine M. (2020)
The study aimed to determine the abundance and diversity of thrips on ?Carabao? mango, Mangifera indica L., at Hacienda Villa Bianca in Maguilling, Piat, Cagayan, Philippines. Thirty (30) mango trees of various ages were selected randomly and grouped into Center, North, East, West, and South with six mango trees per group. Thrips were collected weekly from February? March 2020 from five randomly selected flowering twigs per tree by flower shaking/tapping method. Thrips were sorted and examined under the microscope. Climate data were obtained from the Philippine Atmospheric, Geophysical, and Astronomical Services Administration (PAGASA). A total of 3,100 adult thrips collected were represented by Thrips hawaiiensis (Morgan) (98.581%), Scirtothrips dorsalis Hood (1.097%), Megalurothips usitatus (Bagnall) (0.290%), and Haplothrips gowdeyi (Franklin) (0.032%). M. usitatus and H. gowdeyi are new records on mango in the Philippines. Analysis of variance (ANOVA) between thrips counts per group was not significantly different while counts of four thrips species showed a significant difference (p < 0.05). The thrips were distributed equally and dominated by T. hawaiiensis. The existence of the thrips was positively correlated with temperature and weakly correlated with relative humidity. Thrips were most diverse in the North group, followed by the East, West, Center, and South based on Shannon?s diversity index.
Includes bibliographical references (pages 1027-1028)
Keywords: Haplothrips gowdeyi; Megalurothrips usitatus; Scirtothrips dorsalis; Terebrantia; Thrips hawaiiensis; Tubulifera